2010
DOI: 10.1186/1471-2199-11-49
|View full text |Cite
|
Sign up to set email alerts
|

Sodium butyrate enhances the cytotoxic effect of cisplatin by abrogating the cisplatin imposed cell cycle arrest

Abstract: BackgroundHistone deacetylase inhibitors have been proposed as potential enhancers of the cytotoxic effect of cisplatin and other anticancer drugs. Their application would permit the use of lower therapeutic doses and reduction of the adverse side effects of the drugs. However, the molecular mechanisms by which they sensitize the cells towards anticancer drugs are not known in details, which is an obstacle in developing effective therapeutic protocols.ResultsIn the present work, we studied the molecular mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 37 publications
6
17
0
Order By: Relevance
“…It has been reported that different HDACi sensitize tumor cells towards the killing effect of many anticancer agents (11,(45)(46)(47) and this effect has been attributed to interference with DNA repair pathways (8,11,48) or abrogation of the cell-cycle checkpoints (18)(19)(20). Our results suggest that the accumulation of intracellular ROS-mediated increase in the lesion burden may be the major mechanism by which sodium butyrate enhances the cytotoxicity of MMC-treated cells.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…It has been reported that different HDACi sensitize tumor cells towards the killing effect of many anticancer agents (11,(45)(46)(47) and this effect has been attributed to interference with DNA repair pathways (8,11,48) or abrogation of the cell-cycle checkpoints (18)(19)(20). Our results suggest that the accumulation of intracellular ROS-mediated increase in the lesion burden may be the major mechanism by which sodium butyrate enhances the cytotoxicity of MMC-treated cells.…”
Section: Discussionmentioning
confidence: 50%
“…Recently, it has been reported that sodium butyrate could abrogate the G 1 -S checkpoint activated by cisplatin, force cells in S-phase with damaged DNA, and thus, promote cell killing (20). On the other hand, sodium butyrate was not able to abrogate the G 2 phase checkpoint induced in gamma-irradiated HeLa cells (8) indicating that different cell-cycle arrest points have different sensitivities to HDACi modulation.…”
Section: Introductionmentioning
confidence: 99%
“…Another HDAC inhibitor, sodium butyrate, also sensitized HeLa cells to cisplatin. [171]. Cells exposed to this drug were about two-fold more sensitive to cisplatin than cells exposed to cisplatin alone.…”
Section: Cisplatinmentioning
confidence: 95%
“…Indeed, there has been no definitive study to examine the effect of cisplatin on G1-phase Cdk complexes, particularly in parallel with S- and G2/M-checkpoint responses. Where G1-arrest by cisplatin has been reported, these are largely observed in p53-defective cells (e.g., HeLa cells [15]) and/or at high cisplatin concentrations (e.g., N5 μM [13,15]), the mechanism for which is not understood. Therefore, to examine the potential of G1-checkpoint response with cisplatin, we have undertaken a systematic biochemical and molecular analysis in ovarian p53-proficient A2780 cells, and used DAP as a positive control for G1-arrest and a negative control for S- and G2/M-arrest in this tumor model system [9,16].…”
Section: Introductionmentioning
confidence: 99%